Association of Environmental Factors with Stunting in Biromaru Health Center, Sigi Regency - Syahadat, Dilla Srikandi (Tadulako University, 2025)
Stunting is a major concern in public health. The prevalence of stunting according to 2021 data for each community health center work area in Sigi Regency, the Bureaumaru Community Health Center is at the highest, namely 377 cases (20.9%). This study aims to analyze the relationship between environmental risk factors and the incidence of stunting in the work area of ​​the Bureaumaru Health Center, Sigi Regency. This research was conducted using quantitative methods, cross-sectional study design. The population in this study was 308 people, the sample was 174 respondents. Sampling used the cluster random sampling method in 18 villages. Data were analyzed using univariate and bivariate. The results of analysis using the chi square test with a confidence level of 95%, showed that the ρ value for the variables of hand washing habits, availability of clean water sources and availability of toilets was less than 0.05. Based on findings from research results regarding the relationship between environmental factors and the incidence of stunting in the work area of ​​the Bureaumaru Health Center, Sigi Regency, it can be stated that there is a correlation between the habit of washing hands (ρ = 0.000), the availability of clean water sources (ρ = 0.000), and the condition of latrines (ρ = 0.001) with the prevalence of stunting in children under two years of age in the area.